COMPARATIVE ANALYSIS OF THE DIFFERENTIATION OF WAGE RATES IN RUSSIA AND IN THE UNITED STATES - S. N. Ivashkovski; A. A. Kasparian (Пищевые системы, 2022)
The purpose of this study is a comparative analysis of the factors affecting the differentiation of wage rates in Russia and the United States. The information base for the study was statistical and analytical materials given on the official websites of the Russian Federation and the United States. The article presents an extensive analysis of the wage levels depending on the professional training of employees. Based on statistical data, the authors substantiate why in Russia and the United States the wages of employees with higher professional education are significantly higher than the wages of employees with secondary education, not to mention employees without secondary education. Much attention is paid to the consideration of the differentiation of wage levels with respect to the type of the economic activity. It is shown that in Russia and the United States, despite significant differences in the structure of the economy and economic potentials, the highest earnings prevail in the extractive industries, primarily in the fuel and energy complex. On the other hand, wages in the light and food industries, as well as in agriculture in Russia and the United States are about 20 and 33% of the above-mentioned industries, respectively. The article also examines the differentiation of wages in relation to racial characteristics and gender differences. Citing a number of factual data from Russia and the United States, the authors show that such differentiation in the 21st century should be qualified in terms of labor market imperfections from both scientific and social points of view. The regional aspect of the wage difference in both countries is also analyzed in detail. It is explained why the regional factor has almost no effect on the size of the average wage in the United States contrary to Russia. It is concluded that the most effective mechanism for regulating wage levels is competition in the labor market, which puts the qualifications, skills and experience of employees, as well as working conditions, as the basis for wage differentiation.